A prospective longitudinal study of serum testosterone, dehydroepiandrosterone sulfate, and sex hormone-binding globulin levels through the menopause transition - Burger, H G; Dudley, E C; Cui, J; Dennerstein, L; Hopper, J L (The journal of clinical endocrinology and metabolism, 2000)
The aims of this study were to describe, in relation to date of final menses, the average androgen levels of women in the years before and after this date, and to determine the extent to which these average levels were dependent on age and body mass index (BMI) and the degree of tracking in residual androgen levels, or the extent to which individuals above (below) the mean for their age or time relative to final menstrual period (FMP) and BMI remain above (below) the mean as time progresses. Serial levels of serum sex hormone-binding globulin (SHBG), testosterone (T), and dehydroepiandrosterone sulfate (DHEAS) were measured annually in 172 women from the Melbourne Women's Midlife Health Project who experienced a natural menopause during 7 yr of follow-up. Fasting blood samples were drawn between days 4-8 if women were still menstruating or after 3 months of amenorrhea. The free androgen index (FAI) was calculated as the ratio ofT to SHBG x 100. Means of the log-transformed androgen levels were analyzed as a double logistic function of time relative to FMP as well as age and BMI, and correlations between repeated androgen levels were measured. Mean SHBG levels decreased by 43% from 4 yr before to 2 yr after the FMP. The time of most change was 2 yr before FMP [95% confidence interval (CI), 0.8-3.2]. SHBG levels were, on the average, 5% lower for each halving of estradiol (E2) levels and 4% lower for each kilogram per m2 of BMI (P < 0.0001). About one third of the decline in SHBG was explained by E2 and BMI. After adjusting for all variables, SHBG showed strong tracking. Mean T levels did not vary with time relative to FMP and were independent of age and BMI. Residual values of T showed weak tracking. The FAI increased by 80% from 4 yr before FMP to 2 yr after FMP, and changed maximally 2.2 yr before FMP (95% CI, 1.2-3.2). The FAI was not related to age or E2, but was, on the average, 4% higher for each kilogram per m2 of BMI (P < 0.0001). Residual values of FAI showed moderate tracking. Mean DHEAS levels were not related to the FMP, but were 1.5% lower for each year of age (P < 0.01) and 3.8% lower for each kilogram per m2 of BMI (P < 0.0001). Residual values of DHEAS showed strong tracking. It is concluded that SHBG and FAI levels change at the time of the menopause, at least partially due to the decline in E2. DHEAS decreases as a function of age, not time relative to FMP, and T remains unchanged during the menopausal years. SHBG and DHEAS show a high degree of stability within an individual over time.